A prospective study examining trigger factors and hormonal abnormalities in adult female acne - Prekshi Bansal; Kabir Sardana; Gauri Vats; Lokesh Sharma; Umesh Chandra Garga; Ananta Khurana (Wolters Kluwer Medknow Publications, 2020)
Background: Numerous triggers have been implicated in adult female acne including endogenous (hormonal dysfunction and genetic predisposition) and exogenous causes (drugs, cosmetics, sunscreens, stress, and smoking). Aims: To evaluate the role of various trigger factors in adult female acne and to analyze the androgenic hormone pattern including anti-Mullerian hormone (AMH) in these patients. Materials and Methods: Patients having acne of age ≥25 years were analyzed using a pre devised proforma to elicit trigger factors while the severity was graded using the Global Acne Grading System (GAGS). A detailed hormonal assessment was undertaken that assessed total testosterone (TT), sex hormone-binding globulin (SHBG), free androgen index (FAI), AMH, 17-hydroxyprogesterone (17-OHP), dehydroepiandrosterone sulfate (DHEAS), follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid-stimulating hormone (TSH), and prolactin. Results: Out of the 165 cases seen and sub-analyzed for triggers, premenstrual flare, diet, cosmetics, and stress were the most commonly implicated causes. Among cosmetics, fairness creams and foundations were implicated.The hormonal analysis revealed deranged values of all hormones with the most common being 17-OHP and AMH. Almost 42.8% patients with DHEAS derangement and 58.75% females with raised 17-OHP suffered from moderate to severe stress. Limitations: A prospective cohort correlation study of the implicated triggers is needed to confirm the association with adult female acne. Conclusions: Adult female acne may be triggered by diet, stress, and cosmetics and there is a distinct hormonal milieu that accounts for hyperandrogenemia. We noted high levels of adrenal androgens which have been known to be associated with stress and sleep deprivation. Our study shows the value of counseling adult female acne patients about various acne triggers.